Proposed new upgrading work for UiTM’s dining hall / Ahmad Raedi Ruhazam - Ruhazam, Ahmad Raedi (Faculty of Architecture, Planning and Surveying, 2007)
Since the beginning of the student union movement in the universities, dining hall have been concerned with the provision of the right facility, needs planning and environment suitable for student community. Many facilities of social gathering student activities, international movement, business outlet and entertainment, food outlets, storage, location, and service have been neglected and being unimportant campus spaces. Today this drive to review Student Centre space, environment and services through improvement and revitalization to the current facilities is still very much alive. The goals of this research were to explore, illustrate and observe current state of the art facility and design in Student Centre environments for campus student and administrative at campus community. The research will focusing the study of the need of the right support facilities, physical ambience and environment and requirements of the design project brief for interior design to the facility. It was aim to establish the requirements of design project brief to show how the planning and design process in translating into an environment. It is also to define a new approach and criteria towards attractive Environmental Dining Hall.